PENGARUH PENERAPAN METODE INDEX CARD MATCH TERHADAP HASIL BELAJAR PAI PESERTA DIDIK KELAS VIII SMPN 4 KLARI - Febriyanti Ilyas, Dwi Intan; Kasja Eki Waluyo; Abdul Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning outcomes and limited active participation in the classroom remain common issues, particularly in Islamic Education learning which is often dominated by conventional teaching methods. This study aims to analyze the effect of the Index Card Match (ICM) method on students’ learning outcomes in Islamic Education among eighth-grade students at SMPN 4 Klari. This research employed a quantitative approach with an experimental method, involving 86 students divided into experimental and control groups. Data were collected through questionnaires, observations, and documentation, and analyzed using descriptive and inferential statistics, including normality, linearity, homogeneity tests, and the Independent Samples t-Test. The results indicate that the implementation of the ICM method falls into the moderate category with an average score of 48.02, while students’ learning outcomes are in the moderate to high category with an average of 122.50. The hypothesis test shows a significance value of 0.000 < 0.05, indicating a significant effect on student learning outcomes. Therefore, the Index Card Match method is proven to be effective in improving learning outcomes by enhancing student engagement in the learning process.